Pembelajaran Menggambar Potret Dengan Aplikasi Berbasis Vektor Bagi Siswa Jurusan DKV di SMKN 11 Semarang - Mohamad Daffa Firmansyah, Supatmo; Supatmo (Eduarts: Jurnal Pendidikan Seni, 2024)
Human identity cannot be separated from the shape of their faces, human faces are a creation of God which can provide differences between one human and another. One form of interpretation of the human face in this fine art is a face/portrait image. Currently, portrait images can be created using various tools, media and techniques in the work, one of which is vector-based images assisted by Adobe Illustrator software, CorelDraw. , and ibis paint. This is interesting to study and find out about the process of implementing artistic creation in learning at school. This research aims to explain the preparation, implementation process and analyze the results of work in learning to draw portraits using vector-based applications at SMKN 11 Semarang. This research uses Qualitative Research. Data collection techniques in this type of research use observation, interviews and document tracing. The data obtained was then analyzed through several stages, namely data reduction, data presentation and data verification. The results of the research show that (1) in preparation for learning, teachers, schools and students have prepared various things before starting the learning process, such as school facilities and equipment, applications used in work, and learning tools that must be prepared by teachers before learning begins. . (2) The process of learning to draw portraits using vector-based applications carried out by class (3) The results of the learning process provide information that class